2002
DOI: 10.1051/parasite/2002092167
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitoses among Wayampi Indians from French Guiana

Abstract: Summary :Intestinal parasitism and its epidemiological characteristics were studied in an isolated Amerindian population from Upper Oyapock (French Guiana) that has retained its traditional social and cultural specificities. This population consisted of 138 Wayampi Indians, 68 adults and 70 children (below the age of 15 years), with a sex ratio (M/F) of 0.86, spread over the four villages of the community of Trois Sauts, corresponding to more than two thirds of the population recorded as inhabiting the sector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…High prevalence of hookworm disease was also previously described on this area [11, 36, 37]. This reflects the multifactorial dynamics of waterborne disease in tropical area, including human behavior (water consumption, occupational activity) and malnutrition in precarious conditions of this exposed population [38].…”
Section: Discussionsupporting
confidence: 62%
“…High prevalence of hookworm disease was also previously described on this area [11, 36, 37]. This reflects the multifactorial dynamics of waterborne disease in tropical area, including human behavior (water consumption, occupational activity) and malnutrition in precarious conditions of this exposed population [38].…”
Section: Discussionsupporting
confidence: 62%
“…The results of investigations in Asian countries showed that the prevalence of E.histolytica/E.dispar among handicappeds was 1.8% in Korea (19), in Taiwan 1.1% (13) (23) .The prevalence of E.histolytica/E.dispar in our study was almost similar to that found in French Guiana and Nepal (15,21), but was higher than the reports from Asia and the U.S.A (13,19,20) and lower than what reported in Philippines, Japan, Italy (14,22,23). The prevalence of E.vermicularis in our study was twice to that found in Korea 20.6% [19], but was very higher than reported in the U.S.A 4.5% (20).…”
Section: Discussionsupporting
confidence: 78%
“…The high prevalence of these infections is closely correlated with lack of sanitation, lack of access to safe water, improper food preparation, improper hygiene and impoverished health services (Albonico et al, 1993). Several studies have reported that the people most infected with intestinal and liver parasites are rural residents, especially those in developing countries in, for example, Africa (Koukounari et al, 2008;Nyarango et al, 2008), Asia (Harinasuta et al, 1976;Sithithaworn et al, 2006;Mehraj et al, 2008;Sayasone et al, 2009), and South America (Carme et al, 2002;Carvalho-Costa et al, 2007). The northeast region of Thailand is a mostly dry geographical area and, in socioeconomic terms, has been the most impoverished part of the country for decades.…”
Section: Introductionmentioning
confidence: 99%